Labeling of packaged foods in Brazil: Use of terms such as homemade, traditional, and the like - Corrêa Inácio MACHADO, Priscilla; Martins dos SANTOS, Andréia; Lazzarin UGGIONI, Paula; FABRI, Rafaela Karen; MÜLLER, Jéssica (Revista de Nutrição, 2023)
Objective The study aimed to shed light on the use of the terms “homemade”, “traditional”, and other similar terms in the front-of-pack labels of industrialized foods. Methods Labels of all packaged foods products (n=5,506) available for sale in a Brazilian supermarket were analyzed. The analysis verified the relative and absolute frequency of terms according to the similarity of expressions and semantics by food groups according to Brazilian regulation (nº 359/2003). A chi-square test identified differences in the total food terms with terms between food groups (p<0.001). Results Of all foods analyzed, 14.1% (n=778) presented the target terms. On the analyzed labels, the age of the brand or product was found more frequently (58.1%, n=495), followed by the terms “traditional” (20.1%, n=175) and “original” (11.0%, n=94). The groups that presented the highest relative frequency were groups I (baking goods) and II (canned vegetables), both with 21.4%. Conclusion The study confirmed the commercialization of packaged foods with terms that refer to a traditional and homemade production with different connotations. The information contained in the labels should be clear and correct to ensure that the consumer can make informed choices. The findings indicate the importance of investigating consumers’ perception of the presence of these terms on labels and clarifying the composition of these foods.